51.1k views
2 votes
5n + 3(8 - n) = 66
Solve for n
Show your work

(20 points)

2 Answers

5 votes

Answer:

21

Explanation:

5n+3(8−n)=66

Step 1: Simplify both sides of the equation.

5n+3(8−n)=66

5n+(3)(8)+(3)(−n)=66(Distribute)

5n+24+−3n=66

(5n+−3n)+(24)=66(Combine Like Terms)

2n+24=66

2n+24=66

Step 2: Subtract 24 from both sides.

2n+24−24=66−24

2n=422n

2

=

42

2

n=21

User Aventinus
by
5.6k points
1 vote

Answer: n = 21

Step-by-step explanation: To solve for n in this equation, our first step is to simplify the left side by distributing the 3 through both terms inside the parentheses.

When we do that,

we get 3 times 8 which is 24 and 3 times -n which is -3n.

So we have 5n + 24 -3n = 66.

You can simplify the left side one step further

by combing 5n - 3n to get 2n.

So we have 2n + 24 = 66.

Our next step is to isolate the n term by subtracting 24 from both sides. On the left, 24 - 24 cancels and we're left with 2n. On the right, 66 - 24 simplifies to 42.

So now we have 2n = 42.

Now divide both sides by 2 and n = 21.

User Colin Smith
by
5.0k points